Modification of CSE-UCLA Model Using Weighted Product in Optimizing Digital Library of Learning Support - Dewa Gede Hendra Divayana (Journal of Education and Learning (EduLearn), 2018)
The purpose of this research was to know the implementation of the design model evaluation of CSE-UCLA (Center for the Study of Evaluation-University of California in Los Angeles) modified by the weighted product method into an application evaluation and conduct field trials against simulation application in order to obtain a reliable application used in evaluating digital library services as a complementary learning process at a computer college in Bali. The method that was used in this research was R and D, with a model design of the Borg and the Gall consists of 10 development stages. However, specialized on research this year implemented making the application and field trials as a form of implementation of the draft models that have been produced the previous year. The subject of the research involved in the simulation field trials as much as 2 education experts and 2 informatics experts. Technical analysis in this research was descriptive statistics. The results obtained in this research in the form of applications that have been tested and ready to use for the test on the more respondent and wider coverage.